Nonconvulsive Status Epilepticus on Electroencephalography: An Atypical Presentation of Subacute Sclerosing Panencephalitis in Two Children. (8th October 2012) - Singhi, Pratibha; Saini, Arushi Gahlot; Sahu, Jitendra Kumar
Abstract : Subacute sclerosing panencephalitis is a neurodegenerative disease secondary to measles infection that usually has a typical presentation with progressive myoclonia, cognitive decline, and periodic slow-wave complexes on electroencephalography. We report two pediatric cases who presented with periodic myoclonic jerks and cognitive decline. In both cases, the electroencephalogram showed continuous nonconvulsive status epilepticus activity. Both had elevated measles antibodies in cerebrospinal fluid and blood. Pediatricians need to be aware of this atypical presentation of subacute sclerosing panencephalitis.